Factors associated with delayed initiation of breastfeeding: a survey in Northern Uganda. Issue 1 (1st January 2017) - Mukunya, David; Tumwine, James K; Nankabirwa, Victoria; Ndeezi, Grace; Odongo, Isaac; Tumuhamye, Josephine; Tongun, Justin Bruno; Kizito, Samuel; Napyo, Agnes; Achora, Vincentina; Odongkara, Beatrice; Tylleskar, Thorkild
ABSTRACT: Background : Initiation of breastfeeding later than 1 hour after birth is associated with increased neonatal morbidity and mortality. Objective : To determine the prevalence and factors associated with delayed initiation of breastfeeding. Methods : We conducted a survey in 2016 of 930 children under the age of 2 years in Lira district, northern Uganda. Mothers of the children were interviewed and data was collected on mobile phones using Open Data Kit software (https://opendatakit.org ). Multivariable logistic regression was used to determine factors associated with delayed initiation of breastfeeding. Results : Almost half [48.2%, 95% confidence interval (CI) (44.3–52.1)] of the mothers delayed initiation of breastfeeding. Factors significantly associated with delayed initiation of breastfeeding in multivariable analysis included caesarean delivery [Adjusted Odds Ratio (AOR) 11.10 95% CI (3.73–33.04)], discarding initial breast milk [AOR 2.02 95% CI (1.41–2.88)], home delivery [AOR 1.43 95% CI (1.04–1.97)] and mother being responsible for initiating breastfeeding as compared to a health worker or relative [AOR 1.73 95% CI (1.33–2.26)]. Mothers having a secondary education were less likely [AOR 0.54 95% CI (0.30–0.96)] to delay initiation of breastfeeding as compared to those with no education. Conclusion : About half the mothers delayed initiation of breastfeeding until after 1 hour after birth. Programs to promote, protect and support breastfeeding in this post conflict region are urgently needed.